Wood Dust and Risk of Leukemia: A Protocol of Systematic Review and Meta-Analysis - Soleimani, Yaser; Daraei, Mahdi; Sadeghi, Parniyan; Khazali, Alireza; Rostami, Hanieh; Mahmoudi, Sheyda; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Environment and Cancer, 2024)
Background: Leukemia is a type of cancer caused by the growth of blood cells, especially in the bones and blood. Although extensive research has investigated various environmental factors that increase the risk of leukemia, the relationship between dust exposure and leukemia remains a topic of interest. Wood dusting is a common activity in industries such as carpentry and woodworking, and its potential link to leukemia warrants a comprehensive review to evaluate the available evidence. Understanding this organization is important for occupational health and safety advice and will assist in prevention strategies for those at risk. Methods: We conducted a systematic review and analysis of the existing literature on the relationship between wood dust and leukemia. A comprehensive search of electronic databases, including PubMed, Scopus, and Web of Science, was conducted to identify relevant studies up to the date of review. Methods included peer-reviewed literature, cohort studies, case-control studies, and meta-analyses of peer-reviewed studies such as chip injury and leukemia. Priority will be given to studies with clear evaluation criteria and strong analytical ability. Results: The review identified a total of [X] studies that met the inclusion criteria. These studies reveal different groups of people and workplaces with different levels of wood dust. The extracted data showed various associations between wood dust and leukemia, including positive, negative or neutral effects. Meta-analyses were conducted to provide a synthesis of the available evidence. Subgroup analysis was based on characteristics such as study design, population characteristics, and dust levels. A sensitivity analysis was performed to evaluate the effectiveness of all outcomes. Potential sources of heterogeneity between studies were explored and the quality of evidence was assessed by design.